The design and evaluation of a peripheral device for use with a computer game intended for children with motor disabilities. Issue 1 (January 2015) - Scardovelli, Terigi Augusto; Frère, Annie France
Highlights Webcam with supervisory system was developed to allow computer access for people with disabilities. The developed system converts webcam images in command to control a computer game. Virtual game that provides fun without requiring click and drag action. The system provides fun for children with motor difficulties without causing discomfort or embarrassment.